2018
DOI: 10.1016/j.cma.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

How to control the crack to propagate along the specified path feasibly?

Abstract: A controllable crack propagation (CCP) strategy is suggested. It is well known that crack always leads the failure by crossing the critical domain in engineering structure. Therefore, the CCP method is proposed to control the crack to propagate along the specified path, which is away from the critical domain. To complete this strategy, two optimization methods are engaged. Firstly, a back propagation neural network (BPNN) assisted particle swarm optimization (PSO) is suggested. In this method, to improve the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…To the best of the authors' knowledge, there has not been any study in the literature on determination of the loading conditions that reconstruct a specific crack propagation path in a fractured component. Although there are a few studies on controlling the crack growth path in a body by manipulating its geometry 27 or the applied boundary force direction, 28 the purposes of such works are different from that of the present study. The issue of load identification in a cracked component is of high importance from the structural-health monitoring point of view and failure analysis of an engineering component.…”
Section: Introductionmentioning
confidence: 90%
“…To the best of the authors' knowledge, there has not been any study in the literature on determination of the loading conditions that reconstruct a specific crack propagation path in a fractured component. Although there are a few studies on controlling the crack growth path in a body by manipulating its geometry 27 or the applied boundary force direction, 28 the purposes of such works are different from that of the present study. The issue of load identification in a cracked component is of high importance from the structural-health monitoring point of view and failure analysis of an engineering component.…”
Section: Introductionmentioning
confidence: 90%
“…To our knowledge, few writing works have reported the mechanism of crack propagation in crystalline metal materials with void or inclusion. In particular, the effect of voids and inclusions on crack propagation has never been reported on the microscopic scale while some literature indicated that voids and inclusions could change the path of crack propagation at the macroscopic scale [29,30,31]. In this study, the mechanical properties of the crack propagation for pre-cracked mono-crystals with voids and inclusions have been investigated by MD simulations.…”
Section: Introductionmentioning
confidence: 97%
“…In this group of algorithms, it is worth pointing out widely used ones to predict parameters, such as Simulated Annealing [27], Ant Colony Optimization [17,30], Cuckoo Search [64,13], Wind Driven Algorithm [5,2], Tree-Seed Algorithm [26,7], Water Wave Optimization [67,45], Tree-Growth Algorithm [12], Sailfish Optimizer [44] and Manta Ray Foraging Optimization [66]. Due to easy of implementation, exploration and exploitation search, convergence speed and operational versatility, these algorithms have become popular in parameter estimation in several applications, such as crack propagation [11], design of heat exchangers [15], photovoltaic systems [53], power control of wind turbine [6], strategic aircraft deconfliction [14], optimal power flow problems [3], hybrid renewable systems [41] and others.…”
Section: Introductionmentioning
confidence: 99%